Intraempreendedorismo feminino no setor público: comportamentos de liderança e a superação de barreiras - Silva, Flávia Maria da (2024)
The general objective of this thesis was to investigate how barriers and facilitators affect leadership behaviour in the development of female intrapreneurship in the public sector. The research focused on female mayors who won the SEBRAE "Entrepreneur Mayor" Award (PSPE), exploring the affective and cognitive aspects that impact their leadership behaviour. The methodology adopted was qualitative and exploratory, with an interpretivist nature. Data were collected using complementary questionnaires and semi-structured interviews with six award-winning mayors. The data were analysed using specific software for qualitative analysis, applying Yukl et al.'s (2002, 2012) Hierarchical Taxonomy of Leadership Behaviour, which categorised leadership behaviours into four essential dimensions: task orientation, relations, change, and external leadership. The results revealed that the mayors faced significant barriers such as gender prejudice, bureaucracy, and budget constraints. However, they managed to overcome these barriers through collaborative and inclusive leadership behaviours, demonstrating resilience, innovation, and emotional skills. The research also highlighted the importance of balancing affective and cognitive aspects in leadership behaviour and emphasised the need for public policies and strategies that support female intrapreneurship in the public sector. This thesis expanded the literature by exploring the intersection between leadership, intrapreneurship, and gender in the public sector, providing valuable insights into the leadership practices of female intrapreneurs in governmental contexts.